2007
DOI: 10.1523/jneurosci.2970-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaFragile X Mental Retardation Protein and Metabotropic Glutamate Receptor A Convergently Regulate the Synaptic Ratio of Ionotropic Glutamate Receptor Subclasses

Abstract: A current hypothesis proposes that fragile X mental retardation protein (FMRP), an RNA-binding translational regulator, acts downstream of glutamatergic transmission, via metabotropic glutamate receptor (mGluR) G q -dependent signaling, to modulate protein synthesis critical for trafficking ionotropic glutamate receptors (iGluRs) at synapses. However, direct evidence linking FMRP and mGluR function with iGluR synaptic expression is limited. In this study, we use the Drosophila fragile X model to test this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 97 publications
(137 reference statements)
3
63
0
Order By: Relevance
“…Lgl also interacts with FMRP (fragile X mental retardation protein), an RNA-binding protein that regulates translation of synaptic proteins (Tessier and Broadie 2012). In mutants of dfmr1, A-type receptors accumulate at the expense of B-type receptors, resulting in a shift of GluR composition (Pan and Broadie 2007). Interestingly, Lgl has been shown to interact with FMRP in regulating NMJ architecture and to form a complex with FMRP and mRNAs (Zarnescu et al 2005) Furthermore, mammalian FMRP has been shown to bind the mRNA of lgl and dlg homologs (Darnell et al 2011).…”
Section: Ionotropic Glutamate Receptors At the Nmjmentioning
confidence: 99%
See 1 more Smart Citation
“…Lgl also interacts with FMRP (fragile X mental retardation protein), an RNA-binding protein that regulates translation of synaptic proteins (Tessier and Broadie 2012). In mutants of dfmr1, A-type receptors accumulate at the expense of B-type receptors, resulting in a shift of GluR composition (Pan and Broadie 2007). Interestingly, Lgl has been shown to interact with FMRP in regulating NMJ architecture and to form a complex with FMRP and mRNAs (Zarnescu et al 2005) Furthermore, mammalian FMRP has been shown to bind the mRNA of lgl and dlg homologs (Darnell et al 2011).…”
Section: Ionotropic Glutamate Receptors At the Nmjmentioning
confidence: 99%
“…Loss of dfmr1 results in overgrowth at synapses and increased synaptic function (Zhang et al 2001). Multiple targets of dFMR1 have been characterized, including Futsch (Zhang et al 2001), GluRs (Pan and Broadie 2007), and the HSPGs Dlp and Sdc, leading to defects in Wg and BMP signaling (Friedman et al 2013). There are likely many more targets of dFMR1 to be identified, and the fly NMJ remains an excellent system to reveal the function of FMRP targets in synaptic organization.…”
Section: Mechanisms Regulating Growth and Plasticitymentioning
confidence: 99%
“…FMRP is an mRNA-binding protein that regulates mRNA stability and translation for a number of synaptic and cytoskeleton-associated proteins (Castets et al, 2005;Lu et al, 2004;Muddashetty et al, 2007;Reeve et al, 2005;Todd et al, 2003;Zalfa et al, 2007;Zhang et al, 2001). FMRP function regulates the activity-dependent control of synaptic connections via intersection with group 1 metabotropic glutamate receptor (mGluR) signaling (Antar et al, 2004;Bear et al, 2004;Ferrari et al, 2007;Huber et al, 2002;Nosyreva and Huber, 2006;Pan and Broadie, 2007;Pan et al, 2008). The synapsopathic clinical manifestations of the disease include mild to severe mental retardation (Penagarikano et al, 2007), delayed and depressed developmental trajectories (Bailey et al, 2001a;Bailey et al, 2001b), deficits in short-term memory (Cornish et al, 2001;Munir et al, 2000), hyperactivity (Einfeld et al, 1991), disordered sleep (Gould et al, 2000), seizures (Sabaratnam et al, 2001), and the cytological presentation of long, immature-looking cortical dendritic spines, indicating inappropriate development and/or failure of pruning and synapse elimination (Hinton et al, 1991;Rudelli et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The primary synaptic model is the neuromuscular junction (NMJ), which displays increased synapse arborization and branching, increased synaptic bouton number, and elevated neurotransmission. As in mammals, Drosophila FMRP (dFMRP) functionally interacts with mGluRmediated synaptic glutamatergic signaling in the regulation of postsynaptic glutamate receptor expression (Pan and Broadie, 2007) and in sculpting presynaptic architecture (Pan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reduced mGluR5 expression also reversed cellular and synaptic phenotypes, such as increased protein synthesis, and also altered hippocampal long-term depression in the FMR1 KO mice. In support of this mGluR hypothesis of Fragile X Syndrome, analysis of double KO Drosophila of dFmr1 (homolog of the human FMR1 gene) and dmGluRA (the Drosophila mGluR) has suggested that these two genes converge to regulate postsynaptic GluR trafficking, synaptic ultrastructure and plasticity, and motor behavior [57][58][59]. 2-methyl-6-(phenylethynyl)-pyridine (MPEP), a potent negative modulator of mGluR5 [60], consistently rescues many FXSrelated deficits in KO mice [50,55,56,[61][62][63], fly [64][65][66] and zebrafish [67], implying the therapeutic potential of FXS using mGluR5 inhibitors.…”
Section: Fragile X Mental Retardationmentioning
confidence: 96%